Two artists go to war – Shaun Gladwell and Ben Quilty - Messham-Muir, Kit (The Conversation Media Group, 2014)
Shaun Gladwell and Ben Quilty – two of Australia’s leading artists – display very different approaches to war at parallel exhibitions opening at Perth’s John Curtin Gallery on Saturday 2 August 2014. Gladwell is Australia’s foremost video installation artist, whose Approach to Mundi Mundi featured at the entrance to the Australia exhibition at the Royal Academy of Art in London last year. Quilty is one of Australia’s best-known contemporary painters, winning the 2011 Archibald Prize for his portrait of Australian artist Margaret Olley. He also won the prestigious Prudential Eye award earlier this year and his major solo exhibition at the Saatchi Gallery in London closes on Sunday 3 August 2014.